2017
DOI: 10.1182/blood-2017-04-778423
|View full text |Cite
|
Sign up to set email alerts
|

SLAMF7-CAR T cells eliminate myeloma and confer selective fratricide of SLAMF7+ normal lymphocytes

Abstract: SLAMF7 is under intense investigation as a target for immunotherapy in multiple myeloma. In this study, we redirected the specificity of T cells to SLAMF7 through expression of a chimeric antigen receptor (CAR) derived from the huLuc63 antibody (elotuzumab) and demonstrate that SLAMF7-CAR T cells prepared from patients and healthy donors confer potent antimyeloma reactivity. We confirmed uniform, high-level expression of SLAMF7 on malignant plasma cells in previously untreated and in relapsed/refractory (R/R) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
159
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(167 citation statements)
references
References 45 publications
7
159
0
1
Order By: Relevance
“…Anti-CD38 and anti-SLAMF7 CAR T cells showed anti-MM effects in preclinical models (47,48), but the expression of both target antigens on other normal tissues including hematopoietic lineages and immune effector cells may cause off-tumor toxic effects limiting their long-term clinical use. Being © 1996-2019 (57), and integrin β7 (58).…”
Section: T-cell Targets For Multiple Myelomamentioning
confidence: 98%
“…Anti-CD38 and anti-SLAMF7 CAR T cells showed anti-MM effects in preclinical models (47,48), but the expression of both target antigens on other normal tissues including hematopoietic lineages and immune effector cells may cause off-tumor toxic effects limiting their long-term clinical use. Being © 1996-2019 (57), and integrin β7 (58).…”
Section: T-cell Targets For Multiple Myelomamentioning
confidence: 98%
“…Clinical trials in multiple myeloma targeting B-cell maturation antigen (BCMA) have proven efficacy and safety of the use of CAR-T in this population [64]. Signaling lymphocyte-activating molecule F7 (SLAMF7), the monoclonal antibody target of elotuzumab, is another promising target in multiple myeloma given its lack of expression outside of hematologic cell line; however, CAR-T targeting this antigen has yet to be used in human clinical trials [65,66]. Many trials of CAR-T in multiple myeloma have shown consistent clinical response but optimization of dose and optimal target antigen still require refinement.…”
Section: Future Directionsmentioning
confidence: 99%
“…Therefore, we consider SB transposition as a key enabling technology in order to make CAR-T cell therapy available on a global scale and in large patient cohorts. We have recently shown that CAR-T cells targeting the alternative myeloma antigen SLAMF7 are effective in pre-clinical models [68]. We are preparing a multi-center clinical trial with SLAMF7-specific CAR-T cells engineered with SB gene transfer (http://www.…”
Section: Car-t Cell Immunotherapy In Hematologic Malignanciesmentioning
confidence: 99%